Pengaruh Pendapatan Asli Daerah (PAD), Dana Alokasi Umum (DAU), dan Dana Alokasi Khusus (DAK) Terhadap Alokasi Belanja Modal Pada Kabupaten/Kota di Pulau Jawa - Yusuf Andrian; Agus Samekto (Jurnal Telaah dan Riset Akuntansi, 2017)
Local revenue (LR), public allocation fund (PAF) and special allocation fund (SAF) represents local revenue sources. The existences of LR, PAF, and SAF cause local government demanded as good as possible in using all those three funds, in realizing through useful development and give satisfaction for society itself. This research purposed to identify the effects of LR, PAF, and SAF on government capital expenditure allocation in municipal/regency in java island period 2012 and 2013. Data collecting method used were documentation and library study with quantitative approach. This research analysis used SMART PLS 2.0. the result of the research indicated that LR and SAF had positive and significant effect on capital expenditure. While PAF did not affected on capital expenditure.KEYWORDS : Local revenue, Public Allocation Fund and Special Allocation Fund,                Capital Expenditure